A search using GEO600 for gravitational waves coincident with fast radio bursts from SGR 1935+2154 - Abac, Adrian; Mapelli, Michela; Rinaldi, Stefano (The astrophysical journal, 2024)
The magnetar SGR 1935+2154 is the only known Galactic source of fast radio bursts (FRBs). FRBs from SGR 1935+2154 were first detected by the Canadian Hydrogen Intensity Mapping Experiment (CHIME)/FRB and the Survey for Transient Astronomical Radio Emission 2 in 2020 April, after the conclusion of the LIGO, Virgo, and KAGRA Collaborations’ O3 observing run. Here, we analyze four periods of gravitational wave (GW) data from the GEO600 detector coincident with four periods of FRB activity detected by CHIME/FRB, as well as X-ray glitches and X-ray bursts detected by NICER and NuSTAR close to the time of one of the FRBs. We do not detect any significant GW emission from any of the events. Instead, using a short-duration GW search (for bursts ≤1 s) we derive 50% (90%) upper limits of 1048 (1049) erg for GWs at 300 Hz and 1049 (1050) erg at 2 kHz, and constrain the GW-to-radio energy ratio to ≤1014−1016. We also derive upper limits from a long-duration search for bursts with durations between 1 and 10 s. These represent the strictest upper limits on concurrent GW emission from FRBs.
Gesehen am 14.10.2025